2011
DOI: 10.1002/marc.201100151
|View full text |Cite
|
Sign up to set email alerts
|

Polytellurophenes

Abstract: Will polytellurophenes bridge the gap between conjugated polymer and inorganic solid-state semiconductors? Polytellurophenes are a virtually unexplored class of conjugated polymer. In this paper, the synthetic methodologies that have been used to prepare polytellurophenes are chronicled. The properties of the resulting polymers are discussed and their potential for use as electronic materials is evaluated. It is far too early to know if these materials will lead to a useful class of thin-film semiconductors, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 66 publications
2
53
0
Order By: Relevance
“…[39][40][41][42][43] Use of heavy chalcogen atoms has been shown to increase charge mobility in organic photovoltaic materials, presumably through the enhanced orbital overlap afforded by the 3p and 4p orbitals of selenium and tellurium atoms, respectively, or through enhanced spin-orbit coupling effects. [44][45][46] Indeed, whereas thiophene-based polymers have larger optical band gaps (1.9 eV in polythiophene vs. 1.5 eV in CdTe 47 ) and much smaller charge mobility values than inorganic semiconductors(0.1 cm 2 ·V -1 ·s in polythiophene vs. 100-1000 cm 2 ·V -1 ·s in indium zinc oxide 48 ), replacing sulfur with selenium reduces the optical band gap to 1.6 eV. [49][50][51] The close stacking of selenium and tellurium is also expected to reduce the impact of disorder in the selfassembly process required for COF synthesis and generate more disperse bands to enhance interchain packing of the framework.…”
mentioning
confidence: 97%
“…[39][40][41][42][43] Use of heavy chalcogen atoms has been shown to increase charge mobility in organic photovoltaic materials, presumably through the enhanced orbital overlap afforded by the 3p and 4p orbitals of selenium and tellurium atoms, respectively, or through enhanced spin-orbit coupling effects. [44][45][46] Indeed, whereas thiophene-based polymers have larger optical band gaps (1.9 eV in polythiophene vs. 1.5 eV in CdTe 47 ) and much smaller charge mobility values than inorganic semiconductors(0.1 cm 2 ·V -1 ·s in polythiophene vs. 100-1000 cm 2 ·V -1 ·s in indium zinc oxide 48 ), replacing sulfur with selenium reduces the optical band gap to 1.6 eV. [49][50][51] The close stacking of selenium and tellurium is also expected to reduce the impact of disorder in the selfassembly process required for COF synthesis and generate more disperse bands to enhance interchain packing of the framework.…”
mentioning
confidence: 97%
“…Theoretical calculations suggest that polytellurophenes should possess interesting properties for optoelectronic applications. [16][17][18][19] Tellurophene derivatives have a lower oxidation potentials than the selenophenes and thiophenes analogs in series Te < Se < S. [ 20 , 21 ] The fi rst indication of tellurophene poly merization was in 1985 by chemical polymerization on FeCl 3 catalyst. [ 22 ] From that time, there are only a few publication where tellurophene derivatives were polymerized and characterized.…”
mentioning
confidence: 99%
“…[ 22 ] From that time, there are only a few publication where tellurophene derivatives were polymerized and characterized. [18][19][20][21][22] The fi rst indication of polytellurophene and polybitellurophene synthesis were done by Otsubo et al, [ 21 ] but conditions of electropolymerization process and lack of characterization of synthesized compound suggested that on the electrode had deposited product of degradation. Very recent review on poly(tellurophenes) and its derivatives was written by Jahnke and Seferos [ 19 ] who are suggesting its potential optoelectronic application.…”
mentioning
confidence: 99%
“…4,9 Particularly noteworthy within the subject matter of this Highlight Review is the formation of well-defined and soluble poly(3-alkyltellurophene)s. 22 The synthetic routes to these novel macromolecules are outlined in Scheme 4, and first involve a multistep, yet general, synthesis of the 3-alkyltellurophenes 11a 11c, which in one instance can be directly electropolymerized to yield poly(3-hexyltellurophene) (13a). In order to generate larger quantities of these polymers, the requisite 2,5-diiodotellurophene monomers 12a12c can be prepared by stepwise deprotonation/iodination of 11a11c with sec-butyllithium as a base, followed by quenching of the in situ-generated dilithiotellurophenes with iodine; 22 this route affords low, yet reproducible, yields of monomer (e.g.…”
Section: New Routes To Tellurium Heterocycles and Post-functionalizatmentioning
confidence: 99%
“…3 In this Highlight Review, the emerging chemistry and optoelectronic properties of tellurophenes will be discussed with particular attention given to how synthetic methodology development has led to a renaissance in this area. 4 …”
Section: Introductionmentioning
confidence: 99%